Soil Moisture and Soluble Salt Content Dominate Changes in Foliar δ13C and δ15N of Desert Communities in the Qaidam Basin, Qinghai-Tibetan Plateau - Niu, Weiling; Chen, Hui; Wu, Jianshuang (Frontiers in Plant Science, 2021)
Changing precipitation and temperature are principal drivers for nutrient cycling dynamics in drylands. Foliar isotopic carbon (C) and nitrogen (N) composition (δ13C and δ15N) are often used to describe the plant’s water use efficiency and nitrogen use strategy in plant ecology research. However, the drivers and mechanisms under differential foliar δ13C and δ15N among plant species and communities are largely unknown for arid high-elevation regions. This study collected 462 leaf samples of ten top-dominant plant species (two or three replicates per species) across 16 sites in 2005 and 2010 to measure the community-weighted means (CWMs) of foliar δ13C and δ15N, northeastern Qaidam Basin, Qinghai-Tibetan Plateau. Our results showed that the CWM of foliar δ15N was higher in 2005 than in 2010 and was lower in the warm-dry season (July and August) than the cool-wet one (June and September) in 2010. Similarly, the CWM of foliar δ13C was higher in 2005 than in 2010, but no difference between warm-dry and cool-wet seasons in 2010. C4 plants have higher δ13C and generally grow faster than C3 species under warm-wet weathers. This might be why the CWM of foliar δ13C was high, while the CWM of foliar δ15N was low in the wet sampling year (2010). The general linear mixed models revealed that soil moisture was the most critical driver for the CWM of foliar δ15N, which explained 42.1% of the variance alone. However, the total soluble salt content was the crucial factor for the CWM of foliar δ13C, being responsible for 29.7% of the variance. Growing season temperature (GST) was the second most vital factor and explained 28.0% and 21.9% of the variance in the CWMs of foliar δ15N and δ13C. Meanwhile, remarkable differences in the CWMs of foliar δ15N and δ13C were also found at the species level. Specifically, Kalidium gracile and Salsola abrotanoides have higher foliar δ15N, while Ephedra sinica and Tamarix chinensis have lower foliar δ15N than other species. The foliar δ13C of Calligonum Kozlov and H. ammodendron was the highest among the ten species. Except for the foliar δ13C of E. sinica was higher than Ceratoide latens between the two sampling years or between the cool-wet and warm-dry seasons, no significant difference in foliar δ13C was found for other species. Overall, the CWMs of foliar δ15N and δ13C dynamics were affected by soil properties, wet-dry climate change, and species identity in high-elevation deserts on the Qinghai Tibetan Plateau.